IMPACT OF MACROECONOMIC FACTORS ON FOREIGN DIRECT INVESTMENT IN GHANA: A COINTEGRATION ANALYSIS - Enu, Patrick; K. Havi, Emmanuel Dodzi; Attah-Obeng, Prudence (European Scientific Journal, ESJ, 2013)
﻿The paper examined the determinants of foreign direct investment inflows to Ghana. The main objective of this study was to find out the major macroeconomic determinants of foreign direct investment in Ghana between the periods 1980 to 2012. All the variables considered were integrated at first order, as a result the Johansen’s cointegration approach was used and the result showed that the variables were not cointegrated. Therefore, the vector autoregressive model was estimated. The result showed that the first past year of foreign direct investment , the last two years of exchange rate and trade openness were statistically significant. Based on the findings we recommend that policies that encourage foreign direct investment, moderate exchange rate depreciation and increasing trade openness should be implemented.